Bringing back the tribe: why we should not abandon the study of tribes in the Arab world - Gao, Eleanor (Frontiers in Political Science, 2024)
Once broadly applied, the term “tribe” has been discredited and is now rarely used in the social sciences. Critics argue that the concept is vague, is evocative of primitive and backwards connotations, and has been inappropriately applied to societies that are not “tribal.” While these criticisms are well-founded and legitimate, I argue in this Perspective piece that we must not abandon the study of tribes in the Arab world. The concept of “tribe” continues to be salient for Arab citizens and one that they aptly assign to themselves. To address criticisms of previous studies, I offer three ways to reform scholarly pursuit on tribes: (1) adopting a thin conception of tribe (2) treating the concept as a dynamic not static unit and (3) being led by on-the-ground reality and not by theoretical biases regarding the applicability of this term.